2017
DOI: 10.1007/s12039-017-1257-7
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated polyborate: A mild, efficient catalyst for synthesis of N-tert-butyl/N-trityl protected amides via Ritter reaction

Abstract: Rapid, efficient and inexpensive method for synthesis of N-tert-butyl/N-trityl protected amides via Ritter reaction of nitriles with tertiary alcohols in the presence of a sulfated polyborate catalyst under solvent-free conditions is described. The catalyst has the advantage of Lewis as well as Bronsted acidity and recyclability without significant loss in catalytic activity along with easy work-up, short reaction time and good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Over the past two decades, vast progresses have been made in the development of new catalysts (such as Lewis acids etc ) and new starting materials for Ritter reaction. For example, Indalkar et al reported the reaction of nitriles with tert ‐butanol to produce N ‐ tert ‐butyl amides catalyzed by Sulfated polyborate. On the other hand, several attractive alternatives including tert ‐butyl aceta, tert ‐butyl bromide and methyl tert ‐butyl ether have been explored as the source of the tert ‐butyl carbocation for the synthesis of N ‐ tert ‐butyl amides.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, vast progresses have been made in the development of new catalysts (such as Lewis acids etc ) and new starting materials for Ritter reaction. For example, Indalkar et al reported the reaction of nitriles with tert ‐butanol to produce N ‐ tert ‐butyl amides catalyzed by Sulfated polyborate. On the other hand, several attractive alternatives including tert ‐butyl aceta, tert ‐butyl bromide and methyl tert ‐butyl ether have been explored as the source of the tert ‐butyl carbocation for the synthesis of N ‐ tert ‐butyl amides.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized catalyst was used in the classical Ritter reaction of nitrile 1 and third-type alcohols 75 to give tert-butyl amide 76 in solvent-free conditions (Scheme 29). [42] In 2017, the various nitriles 1 were treated with tertiary alcohols 75 via Ritter reaction in the presence of H-form Zeolite Y nanoparticle assemblies (HY-NA) to form different amides 76 at 120°C (Scheme 30). [43] In 2015, Biermann's research team provided the asymmetric synthesis of desired sterioseletive amino alcohol 78 through the Ritter reaction of sterioseletive acetonitrile 47 with (1S,2S)-1-(2-chlorophenyl) cyclohexane-1,2-diol 77 (as a product of Sharpless asymmetric dihydroxylation)in the presence of H 2 SO 4 as a catalyst in CH 2 Cl 2 solvent at room temperature (Scheme 31).…”
Section: Using Various Alcohol As Starting Materialsmentioning
confidence: 99%
“…[47][48][49][50][51][52] Its easy preparation, mild acidity, eco-friendliness, and reusability have encouraged us to investigate its potential to catalyze many other useful organic transformations. Therefore, inspired by our previous finding, herein we report a rapid, efficient and green method for synthesis of α-aminonitriles via Strecker reaction using aldehyde, amine, and TMSCN in the presence of a sulfated polyborate as a recyclable catalyst under solvent-free conditions.…”
Section: Scheme 1 Schematic Representation Of Sulfated Polyborate Camentioning
confidence: 99%